THE EFFECT OF PEER COLLABORATION TOWARD ENGLISH WRITING SKILL - Fitri Saniya; Widi Syaftinentias; Destri Wahyuningsih (J-Shelves of Indragiri (JSI), 2026)
This research investigates the effectiveness of the peer collaboration method in enhancing the English writing skills of eleventh-grade students at SMAN 2 Kelayang. The study was prompted by common challenges in writing instruction, including low student motivation and a lack of collaborative learning opportunities. Using a quasi-experimental design, the study compared an experimental class (XI2) treated with peer collaboration against a control class (XI3) taught through conventional methods. Data were gathered via narrative writing pre-tests and post-tests, subsequently analyzed using the Independent Samples T-Test. Findings reveal a significant improvement in the experimental group, with mean scores rising from 40.60 to 77.95, notably higher than the control group’s final score of 58.60. The statistical analysis yielded a Sig. (2-tailed) value of 0.000, confirming that peer collaboration has a significant impact on writing performance. The study concludes that this method not only improves writing quality but also fosters student confidence through interactive feedback. It is recommended that educators implement peer collaboration as a strategic tool to improve English literacy in secondary education.